2009
DOI: 10.3164/jcbn.09-82
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Hesperidin Exerts Hypoglycemic and Hypolipidemic Effects in Streptozotocin-Induced Marginal Type 1 Diabetic Rats

Abstract: Citrus bioflavonoids may offer some protection against the early stage of diabetes mellitus and the development of complications. We investigated the effect of hesperidin on blood glucose levels, hepatic glucose-regulating enzyme activities, serum insulin and adiponectin levels, serum and hepatic lipid levels, and parameters of bone loss in streptozotocin (STZ)-induced marginal type 1 diabetic rats. Weanling male rats were randomly assigned to experimental 3 groups: a control (C) group, a STZ induced marginal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
79
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(93 citation statements)
references
References 23 publications
(30 reference statements)
6
79
1
1
Order By: Relevance
“…Other compounds in the extract could also contribute to the observed hypoglycaemic effect through synergistic or additive effects. Hesperidin, in particular, comprising 0.35% of the honeybush extract, was shown to have a hypoglycaemic effect in marginally hyperglycaemic Wistar rats normalising their blood glucose concentrations after 16 days (Akiyama et al, 2010). Jung et al (2004), using a spontaneously diabetic C57BL/KsJdb/db mouse model, showed that a 5-wk supplementation of the diet with 0.02% hesperidin ameliorated the development of hyperglycaemia in these mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other compounds in the extract could also contribute to the observed hypoglycaemic effect through synergistic or additive effects. Hesperidin, in particular, comprising 0.35% of the honeybush extract, was shown to have a hypoglycaemic effect in marginally hyperglycaemic Wistar rats normalising their blood glucose concentrations after 16 days (Akiyama et al, 2010). Jung et al (2004), using a spontaneously diabetic C57BL/KsJdb/db mouse model, showed that a 5-wk supplementation of the diet with 0.02% hesperidin ameliorated the development of hyperglycaemia in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…Jung et al (2004), using a spontaneously diabetic C57BL/KsJdb/db mouse model, showed that a 5-wk supplementation of the diet with 0.02% hesperidin ameliorated the development of hyperglycaemia in these mice. Both Akiyama et al (2010) and Jung et al (2004) attributed the hypoglycaemic effect of hesperidin to upregulation of glucose regulating enzymes, in particular glucokinase, which enhances glycolysis and increases glycogen synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, several studies indicate that hesperetin is more active than hesperidin. [37][38][39][40][41] In our studies, male NZW rabbits were used. Rabbits have been widely used to study ocular pharmacokinetics of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, hesperidin, naringin and nobiletin also showed hypoglycemic effects by improving insulin sensitivity in diabetic animals (Akiyama et al, 2009;Akiyama et al, 2010;Jung et al, 2006;Jung et al, 2004;Lee et al, 2010). However, whether these citrus flavonoids regulated blood glucose via other target proteins or genes related to diabetes were unclear.…”
mentioning
confidence: 99%